INVENTORY OF SECUDASTER (Holothuroidea) IN NAMTABUNG VILLAGE MALUKU PROVINCE - Tuhumury, Lussy; Suriani, Sanita; Wakano, Deli (RUMPHIUS, 2020)
Coastal waters of Namtabung village sub-district Selaru West Southeastern Moluccas is the water areas that have all kinds of marine biota one of which is Holothuroidea. The coastal waters of Namtabung village are in good condition for the marine organisms lives. This research aims to know the specieses of Holothuroidea in Namtabung village sub-district Selaru West Southeastern Moluccas. Type of the research is descriptive qualitative, with procedures observation and identification. The results of this research there are eight species of Holothuroidea, among there are from Aspidochirotida order with 7 species consist of Holothuria scabra, Holothuria atra, Holothuria edulis, Holothuria leucospilota, Actinopyga lecanora, Stichopus ocellatus and Bohadschia argus, whereas from Apodida order there are only one species that is Synapta maculata